Immunology of AAV-Mediated Gene Transfer in the Eye - Willett, Keirnan L.; Bennett, Jean (Frontiers in Immunology, 2013)
The eye has been at the forefront of translational gene therapy largely owing to suitable disease targets, anatomic accessibility and well-studied immunologic privilege. These advantages have fostered research culminating in several clinical trials and AAV has emerged as the vector of choice for many ocular therapies. Pre-clinical and clinical investigations have assessed the humoral and cellular immune responses to a variety of naturally occurring and engineered AAV serotypes as well as their delivered transgenes and these data have been compared to potential clinical sequelae. Encouragingly, AAV appears safe and effective with clinical follow up surpassing 5 years in some studies. As disease targets continue to expand for AAV in the eye, thorough and deliberate assessment of immunologic safety is critical. With careful study, the development of these technologies should concurrently inform the biology of the immune response in the eye.